Novel Compound Heterozygous DST Variants Causing Hereditary Sensory and Autonomic Neuropathies VI in Twins of a Chinese Family - Jin, Jie-Yuan; Wu, Pan-Feng; He, Ji-Qiang; Fan, Liang-Liang; Yuan, Zhuang-Zhuang; Pang, Xiao-Yang; Tang, Ju-Yu; Zhang, Li-Yang (Frontiers in Genetics, 2020)
Background: Hereditary sensory and autonomic neuropathies (HSAN) are a rare and severe group of sensory axonal neuropathies. HSAN have been classified into eight groups based on inheritance, clinical features and the related genes. And HSAN-VI perhaps is the most notable one. HSAN-VI is an autosomal recessive disease, which manifests the severely impaired pain sensitivity, autonomic disturbances, distal myopathy, spontaneous or surgical amputations, and even early death. Genetic researches indicate that DST is a causative gene. DST encodes dystonin, a member of the plakin proteins family that is involved in cytoskeletal filament networks. Dystonin has seven major neuronal isoforms in nerve, muscle and epithelium. Material and Methods: The present study investigated a Chinese family with HSAN, and explored potential pathogenic variants using whole-exome sequencing (WES). Variants were screened and filtered through bioinformatics analysis and prediction of pathogenic of the variants. Co-segregation were subsequently conducted. Results: We identified the compound heterozygous variants of DST (c.3304G>A, p.V1102I and c.13796G>A, p.R4599H) in two patients. Conclusion: We reported a Chinese HSAN-VI family and detected the disease-causing variants. Our description expands the spectrum of known DST variants and contributes to the clinical diagnosis of HSAN-VI.